Movimientos cabalistas en el mundo global: entre la tradición y la alta modernidad = Kabalist movements in the global world: between tradition and high modernism - Mardero, Lelio Nicolás Guigou (Civitas - Revista de Ciências Sociais)
This article deals with the contemporary movements of beliefs whose cornerstone is based on the Kabbalah tradition, considering the transformations they have experienced in our high modernity. We analyze these movements as producing subjects of the current processes of globalization, to the extent that the globalized and interconnected world constitutes one of the main justifications both of their current characteristics and their actions. From this viewpoint the Kabbalist movement Bnei Baruch and its singular journey are analized, considering its relationship with the Kabbalah tradition and its actual staging through the narratives generated in virtual and real spaces